A Sonochemical Access to 5-Aryl Substituted Pyrazolo[1, 5-a]Pyrimidines as Potential Inhibitors of TNF-α. (7th February 2023) - Prasada Rao, Daliparthi Eswara; David Raju, Medepalli; Ravi Kumar Reddy, Nallamaddi; Rajendiran, Chinnapillai; Sai Praneeth, Muthineni; Tej, Mandava Bhuvan; Basaveswara Rao, Mandava V.; Kapavarapu, Ravikumar; Pal, Manojit
Abstract: In spite of various and extensive studies known for pyrazolo[1, 5- a ]pyrimidines the synthesis, in silico studies and biological evaluation of their 5-(het)aryl analogs remained underexplored. The TNF-α inhibitors on the other hand has considerable therapeutic potential for autoimmune and inflammatory diseases in addition to cancer, diabetes and possibly COVID-19. In the current study 5-aryl pyrazolo[1, 5- a ]pyrimidines were explored as potential inhibitors of TNF-α that was supported by the in silico studies. This class of compounds was accessed via a sonochemical synthesis involving the acid catalyzed cyclocondensation reaction of aminopyrazoles with acrylophenones in the presence of aerial oxygen. The study indicated that the overall rate of the reaction was enhanced by ultrasound in the absence of which a longer duration and higher temperature was necessary. The current catalyst/promoter/ligand free and scalable method afforded a range of compounds. Some of these compounds showed good inhibition of TNF-α in vitro where ester/amide moiety at the C-3 position played a key role in interacting with the protein dimer as suggested by the in silico studies. Indeed, these groups formed H-bonds with A: GLY121 and B: TYR151 residues of TNF-α dimer in silico . A brief SAR within the series and in silico ADME/toxicity prediction for best active compounds is presented. Compounds 3a-c were identified as initial hits for further pharmacological evaluations. Graphical Abstract: UF0001 A sonochemical method has been developed for the facile synthesis of pyrazolo[1, 5- a ]pyrimidines that were evaluated as potential inhibitors of TNF-α.